STRATEGI PENINGKATAN MUTU LEMBAGA PENDIDIKAN NON FORMAL MELALUI IMPLEMENTASI MANAJEMEN MUTU TERPADU - Arfiah Lestari Putri; Achmad Supriyanto (Universitas Pendidikan Indonesia, 2023)
Education has an important role in efforts to develop the nation because through education it will create superior and quality human resources. This study aims to identify and examine how strategies to improve the quality of non-formal educational institutions through the implementation of integrated quality management. The results of the research show that integrated quality management has proven successful in improving the quality of non-formal education institutions. The strategies for implementing integrated quality management that have been successfully implemented by several non-formal educational institutions in Indonesia include: (a) Using strategies that focus on excellence and local wisdom owned by schools; (b) Making improvements or improvements progressively and consistently on various aspects of the educational process; (c) Involving the involvement of all parties in the context of institutional strengthening; (d) Strive to achieve customer satisfaction criteria.